EFEKTIVITAS MEDIA PEMBELAJARAN BERBASIS POWERPOINT TEMA AGAMA DI KB-TK ASSALAMAH UNGARAN KABUPATEN SEMARANG - Hasjiandito, Akaat; Adiarti, Wulan; Wantoro, Wantoro (Jurnal Penelitian Pendidikan, 2016)
Assalamah Playgroup-Kindergarten as one of the early childhood institution seeks to develop innovative learning models by using interactive learning cd developed by teachers. The purpose of this study was to determine the validity of the media developed by teachers and to know how big the effectiveness of instructional media used in learning activities.The method used in this research is to use an experimental method that is pretest-posttest control group design that compares the learning achievement of children before and after treated learning by using power point learning cd and compared between the experimental group and the control group.Results from this study are media generated was declared invalid. It is based on data obtained from experts and materialvalidator. In addition to a valid media used in learning with religious themes on Assalamah Playgroup-Kindergartenin Ungaran also effective in the learning activities, it can be seen from the rise in learning outcomes among students, especially in kindergarten B.